Impact of alkali treatment on physico-chemical, thermal, structural and tensile properties of Carica papaya bark fibers. Issue 6 (18th August 2018) - Saravanakumaar, A.; Senthilkumar, A.; Saravanakumar, S. S.; Sanjay, M. R.; Khan, Anish
Abstract: This study aims to examine the effect of sodium hydroxide (NaOH) treatment on the physico-chemical properties, structure, thermal, tensile and surface topography of Carica papaya fibers (CPFs). The surface of raw CPFs was modified by soaking with 5% NaOH solution for 15, 30, 45, 60, 75 and 90 min. The results of thermo-gravimetric analysis revealed that the optimum treatment time for alkali treatment was 60 min. It was found that the alkali treatment improved the properties of the CPFs. The results of TGA, FT-IR, XRD and AFM suggest that the treated CPF is a suitable alternative as reinforcement in polymer composites.